Foreign Direct Investment, Growth of Output Indicators and Economic Growth in China: Empirical Evidence on Causal Links - Caesar, Ayamba Emmanuel; HaiBo, Chen; Udimal, Thomas Bilaliib; Osei-Agyemang, Andrew (International Journal of Economics and Financial Issues, 2018)
This paper examines the causality between foreign direct investment, growth of output indicators and gross domestic product in China between 1995-2016 using Granger causality test based on the vector error correction model. In contemporary times, attention has been drifted from overall foreign direct investment as engine of growth in the analysis of economic growth to sectoral composition of the economy. This paper considers the growth of output indicators (manufacturing, service and agricultural sectors) as engines of growth. The results indicate a bidirectional causal link between gross domestic product and foreign direct investment in the long and short runs. There was however a uni-directional relation between gross domestic product and manufacturing and service sectors in the long run. A short run causal link exists between gross domestic product and manufacturing but not for service. The study does not confirm causality to run from gross domestic product to agriculture. Keywords: FDI; Economic growth; VECM causality JEL Classifications: F21, F43